Bajeczno-mityczna geneza Portugalii w zwierciadle pierwszej i drugiej części "Monarchia Lusitana" Bernarda de Brito - Działak-Szubińska, Anna (Rome and Iberia : Inspirations and Connections throughout History, 2021)
Tales on the origins of Portugal are based on mythological, biblical and historical motifs. They gain a large degree of resonance in the context of the Iberian Union (1580–1640). From the rich body of works developed in that period there is one that merits closer attention: Monarchia Lusitana – the history of Portugal first taken up by the Cistercians of the Santa Maria de Alcobaça monastery. Following the analysis of the work’s structure and content and by making reference to the research of, among others, Jacek Banaszkiewicz on “de origines”, the present chapter goes over the mythical roots of Portugal as reflected in the first and the second part of the Monarchia Lusitana (1597 and 1609) chronicle project started by Bernardo de Brito (1569–1617).